2022
DOI: 10.1002/jhm.12788
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of utilization and evaluation of advanced practice providers on academic hospital medicine teams: A national survey

Abstract: This survey study aimed to provide a contemporary appraisal of advanced practice provider (APP) practice and to summarize perceptions of the benefits and challenges of integrating APPs into adult academic hospital medicine (HM) groups. We surveyed leaders of academic HM groups. We received responses from 43 of 86 groups (50%) surveyed. Thirty-four (79%) reported that they employed APPs. In most groups (85%), APPs were reported to perform daily tasks of patient care, including rounding and documentation. Less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Unsurprisingly, this study’s findings indicate that APPs perform a myriad of clinical activities in the hospital setting, such as completing the initial admission history and physical examination, writing admission orders and admitting patients to the hospital, and accepting admitted patients for tuck-in. The respondents further reported that APPs provide perioperative management, conduct surgical consultations, perform procedures, perform daily rounding while carrying their own complement of patients, and are involved in discharge planning, which is consistent with previous research [ 7 - 9 ]. It is unknown whether APPs were performing some of these clinical tasks independent of physician supervision.…”
Section: Discussionsupporting
confidence: 87%
“…Unsurprisingly, this study’s findings indicate that APPs perform a myriad of clinical activities in the hospital setting, such as completing the initial admission history and physical examination, writing admission orders and admitting patients to the hospital, and accepting admitted patients for tuck-in. The respondents further reported that APPs provide perioperative management, conduct surgical consultations, perform procedures, perform daily rounding while carrying their own complement of patients, and are involved in discharge planning, which is consistent with previous research [ 7 - 9 ]. It is unknown whether APPs were performing some of these clinical tasks independent of physician supervision.…”
Section: Discussionsupporting
confidence: 87%
“…Many articles highlighted the importance of organisational planning and strategy in APP role development, recruitment, integration, retention and career development. The organisational view of existing workforce shortages [ 37 , 57 ], service gaps [ 58 , 59 ] and anticipated roles and values [ 30 , 44 , 60 62 ] of APPs often influenced whether APPs were recruited and their specific category. For example, this included organisations aiming for service expansion requiring less specialised APPs to meet the increasing demand for lower acuity patients [ 60 ], those intending that APPs take on more quality improvement roles [ 30 , 63 ] when hospital ratings were assessed as low by regulators.…”
Section: Resultsmentioning
confidence: 99%
“…While inpatient APN/PA care models vary, successful integration into a hospital's broader clinical operations has the potential to improve the quality and efficiency of care, promote the development of cohesive interprofessional teams, and reinforce a positive reputation of APN/PAs. 5 , 6 , 7 , 8 , 9 Conversely, a poorly integrated or failed APN/PA service can have detrimental effects on the reputation of APN/PAs and their future use at an institution. APN/PAs continue to be cited as an important resource to combat physician shortages and are increasingly being deployed in acute care inpatient settings in roles that go beyond the traditional extender model and broaden APN/PA autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to an expansion of their clinical roles, the scope of practice, and independence within these roles. While inpatient APN/PA care models vary, successful integration into a hospital's broader clinical operations has the potential to improve the quality and efficiency of care, promote the development of cohesive interprofessional teams, and reinforce a positive reputation of APN/PAs 5–9 . Conversely, a poorly integrated or failed APN/PA service can have detrimental effects on the reputation of APN/PAs and their future use at an institution.…”
Section: Introductionmentioning
confidence: 99%